ISPC Commentary on the Revised Proposal for CRP3.1 - September 2011 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2011)
ISPC Commentary on the revised proposal for CRP 3.1: "WHEAT - Global Alliance for Improving Food Security and the Livelihoods of the Resource poor in the Developing World" (Revision of August 2011).